INCREASING THERMIC EFFICIENCY OF LAND OIL COMPORT BY APPLYING THE HOUSEHOLD EFFECT PRINCIPLES - Jarwo Puspito (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2002)
One of components that could be considered in decreasing the rate ofenergy consumption is the household sector. Most of Indonesian householder, who is in the low up to middle class, uses kerosene as the main source energy in daily cooking. The objectives of this investigation are to study the effects of glass thickness and slope on the degree of kerosene-stove efficiency. The results of this research could be used as input in designing the characteristic of a glass concave . cover, which can produce the highest efficiency of a kerosene stove.Design used in this research was factorial experimental design. The thickness and shape of the glass concave cover was considerable as the speed of heating process, which showed the degree of efficiency, was considered.as dependent variable. As the control variable, were room temperature, the length of stove's wick, water volume, initial temperature of water, observation range of temperature, type of stove, and the kerosene quantity in the stove tank. Based on the research design, data were analyzed by two-direction variance analysis. With this method, it could be shown whether the thickness and slope and the degree of the stove efficiency will be shown graphically. Base on the result of the data analysis, it can concluded that (1) the slope of the glass concave cover affect the degree of the stove efficiency, (2) The thickness of the cover did not effect the degree of the stove efficiency, (3) at the slope of 82 degree, it was shown that the efficiency was maximum, (4) in comparison to unmodified stove, the modified stove with glass concave cover had an efficiency of 25, 8 % higher at the slope of 82 degree.